2021
DOI: 10.1021/acs.joc.1c00613
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of cis-2-Ene-1,4-diones via Aerobic Oxidation of Substituted Furans Catalyzed by ABNO/HNO3

Abstract: We report a highly efficient and selective catalytic system, ABNO (9-azabicyclo-[3.3.1]­nonane N-oxyl)/HNO3, for the aerobic oxidation of substituted furans to cis-2-ene-1,4-diones under mild reaction conditions using oxygen as the oxidant. The catalyst system is amenable to various substituted (mon-, di-, and tri-) furans and tolerates diverse functional groups, including cyano, nitro, naphthyl, ketone, ester, heterocycle, and even formyl groups. Based on the control and 18O-labeling experiments, the possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Beside the starting material 2 d two other major compounds 2 x , y have proton chemical shifts in the 6–6.5 pm range indicating two other furans or the opened intermediates 6 (Scheme 1). The observed chemicals shifts are also similar to the reported but‐2‐en‐1,4‐diones prepared by oxidation of furans [47] and the formation of cyclized compounds similar to the intermediate 7 can also be postulated [48] . The ratio of 2 d – 2 x – 2 y – 9 d – 9 x was determined by 1 H NMR to be 1.3–1.0–0.5–0.6–1.0, suggesting a conversion of furan to pyridine for 2 d of approximatively 36 % with a modest 14 % conversion to the expected pyridinol 9 d .…”
Section: Resultssupporting
confidence: 85%
“…Beside the starting material 2 d two other major compounds 2 x , y have proton chemical shifts in the 6–6.5 pm range indicating two other furans or the opened intermediates 6 (Scheme 1). The observed chemicals shifts are also similar to the reported but‐2‐en‐1,4‐diones prepared by oxidation of furans [47] and the formation of cyclized compounds similar to the intermediate 7 can also be postulated [48] . The ratio of 2 d – 2 x – 2 y – 9 d – 9 x was determined by 1 H NMR to be 1.3–1.0–0.5–0.6–1.0, suggesting a conversion of furan to pyridine for 2 d of approximatively 36 % with a modest 14 % conversion to the expected pyridinol 9 d .…”
Section: Resultssupporting
confidence: 85%
“…193 Recently, Zhang and Xie et al reported the aerobic oxidation of substituted furans into corresponding cis-2-ene-1,4-diones using an ABNO/HNO3 catalytic system. 194 They proposed that this transformation involves the nucleophilic addition of furans at the C2 position to form ABNO oxoammonium species.…”
Section: -6-1 Oxidation Of Phenolsmentioning
confidence: 99%
“…Furan derivatives are readily available and some of them have been identified as platform molecules that can be obtained from renewable resources. [1][2][3] Due to their low aromatic properties, they serve as important building blocks in bioactive molecules, making them valuable in synthetic chemistry. [4][5][6][7] They can not only be used as masked olefins, enol ethers, 8 1,4dione, 9 and carboxylic acids, 10 but can also undergo recyclization reactions to form carbocycles and heterocyclic rings.…”
Section: Introductionmentioning
confidence: 99%